2018
DOI: 10.18178/ijesd.2018.9.12.1130
|View full text |Cite
|
Sign up to set email alerts
|

The Use of GIS and Remote Sensing to Investigate Groundwater Vulnerability to Contamination and Surface Water Susceptibility to Pollution at Mafraq Dumpsite/Jordan

Abstract: This study will evaluate how vulnerable groundwater is to contamination in Jordan, whilst further determining how prone to pollution surface water is. Situated upon what is believed to be one of Jordan's most important groundwater aquifers, the Mafraq dumpsite is understood to be a great hazard to the quality of water. With the ability to thoroughly assess both groundwater and surface water, the DRASTIC and SWSi indexes have been utilized throughout this study, providing further insight into whether the Mafraq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Additionally, MCDM is usually used in combination with GIS to analyse risks, sensitivity mapping, and the priority indexing of resources [27]. Alternatively, both GIS and remote sensing (RS) are used to analyse and predict environmental changes quickly, efficiently, and reliably [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, MCDM is usually used in combination with GIS to analyse risks, sensitivity mapping, and the priority indexing of resources [27]. Alternatively, both GIS and remote sensing (RS) are used to analyse and predict environmental changes quickly, efficiently, and reliably [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the intrinsic vulnerability of groundwater in the study area indicated that the index values ranged from 70 to 203, whereas the Modi ed DRASTIC model including anthropogenic factors indicated control the pollutant diffusion within the aquifer(Al-abadi et al, 2017;Al-adamat, 2018;Bera et al, 2021). Furthermore, an aquifer's vulnerability to groundwater contamination is determined by the susceptibility of its recharge area to in ltration, i.e.…”
mentioning
confidence: 98%